Improving Wildfire Resilience in the Mediterranean Central-South Regions of Chile - Fernando Veloso; Pablo Souza-Alonso; Gustavo Saiz (Fire)
Wildfires in central-south Chile, consistent with trends observed in other Mediterranean regions, are expected to become more frequent and severe, threatening ecosystems and impacting millions of people. This study aims to enhance wildfire resilience in the central-south regions of Chile through the provision of robust information on current wildfire management practices and comparison with successful alternatives implemented in other fire-prone Mediterranean regions. With this aim, we consulted 55 local stakeholders involved in wildfire management, and alongside a comparative analysis of wildfire statistics and resource allocation in selected Mediterranean regions, we critically assessed different strategies to improve wildfire prevention and management in central-south Chile. The comparative analysis indicated notable economic under-investment for wildfire prevention in Chile. Compared to other Mediterranean countries, Chile is clearly below in terms of investment in forest fire prevention, both in global (public investment) and specific terms ($ ha−1, GDP per capita). The experts consulted included fuel management, governance and community participation, territorial management, landscape planning, socioeconomic evaluation, and education and awareness as key aspects for wildfire prevention. The results of the questionnaire indicated that there was a broad consensus regarding the importance of managing biomass to reduce fuel loads and vegetation continuity, thereby enhancing landscape resilience. Landscape planning and territorial management were also emphasized as critical tools to balance ecological needs with those of local communities, mitigating wildfire risks. Fire-Smart management emerged as a nature-based solution and a promising integrated approach, combining fuel treatments with modeling, simulation, and scenario evaluation based on local and regional environmental data. Additionally, educational and social engagement tools were considered vital for addressing misconceptions and fostering community support. Besides a better integration of rural planning with social demands, this study underscores the urgent need to substantially increase the investment and significance of wildfire prevention measures in central-south Chile, which are key to improving its wildfire resilience. Our work contextualizes the reality of wildfires in central-south Chile and directly contributes to mitigating this growing concern by critically examining successful wildfire resilience strategies from comparable fire-prone regions, complementing ongoing local efforts and offering a practical guide for stakeholders in wildfire management and prevention, with particular relevance to central-south Chile and other regions with similar characteristics.